Anticancer activity of mixed Graphene/Carbone nanotubes reinforced Sulfur-Containing polyketoamine nanocomposites - Khalid A. Khan; Gadeer R. Ashour; Mahmoud A. Hussein (Results in Chemistry)
This study reports the successful synthesis of a novel polyketoamine (PKA) and its nanocomposites, including graphene nanosheets (GNS) and multi-wall carbon nanotubes (MWCNT), through an in-situ polycondensation reaction incorporating sulfur and thiazole moieties. A hybrid nanofiller composed of MWCNT and GNS (MWCNT-GNS) was prepared using a straightforward method, serving as a mixed reinforcement in the nanocomposite polymers. The polymerization process utilized 4,4′-bis-chloroacetyl-diphenylsulfide and 4,4′-bis-(2-aminothiazole-4′’-yl)diphenylsulfide in absolute ethanol. The structure and properties of the synthesized materials were comprehensively analyzed through various techniques, including Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetric Analysis (TGA), X-ray Diffraction (XRD), Gel Permeation Chromatography (GPC), and solubility testing. Morphological characteristics were examined using Field Emission Scanning Electron Microscopy (FESEM) and Transmission Electron Microscopy (TEM). This multi-faceted analytical approach provided a thorough understanding of both structural and morphological attributes. The synthesized PKA nanocomposites demonstrated significant antimicrobial and anticancer activities, showcasing their versatile properties and potential applications. Among the materials, PKA/GNS/MWCNTsd exhibited the highest antifungal efficacy, particularly against Candida albicans and Aspergillus flavus, with antifungal activity (inhibition zones measuring 14 and 13 mm) increasing with higher GNS/MWCNT content. The nanocomposites also showed pronounced anticancer effects, with PKA/GNS/MWCNTsa (IC50 = 92.89 μg/mL) being the most effective, followed by PKA/GNS/MWCNTsd (IC50 = 104.0 μg/mL), PKA/GNS/MWCNTsc (IC50 = 109.5 μg/mL), PKA/GNS/MWCNTsb (IC50 = 110.1 μg/mL), and pure PKA (IC50 = 149.4 μg/mL). Methylene blue staining confirmed the suppression of cancer cell growth, particularly with PKA/GNS/MWCNTsd, highlighting their potential for clinical applications.